A Child With Dyserythropoietic Anemia and Megakaryocyte Dysplasia Due to a Novel 5′UTR GATA1s Splice Mutation. Issue 5 (29th December 2015) - Zucker, Jacob; Temm, Constance; Czader, Magdalena; Nalepa, Grzegorz
Abstract : We describe a child with dyserythropoietic anemia, thrombocytosis, functional platelet defect, and megakaryocyte dysplasia. We show that (i) this constellation of hematopoietic abnormalities was due to a germline mutation within the 5′ untranslated region (5′UTR) of globin transcription factor 1 ( GATA1 ); (ii) the mutation impaired a 5′UTR GATA1 splicing site, with promoted production of the shortened GATA1 isoform lacking the N‐terminus; and (iii) expression of the GATA1 N‐terminus is restricted to erythroblasts and megakaryocytes in normal marrow, consistent with the patient's abnormal erythropoiesis and megakaryopoiesis. Our findings provide insights into the clinically relevant in vivo function of the N‐terminal domain of GATA1 in human hematopoiesis.